Assessing Sustainability in Indonesia Fisheries through Local Wisdom Empowerment - Parsaulian, Baginda; Irianto, Agus; Aimon, Hasdi (Journal of Management World, 2025)
This research assessing the sustainability of Indonesian fisheries by utilizing local knowledge and identifying the key factors that significantly contribute to the economic, technological, social, ethical, and governance dimensions through Multidimensional Scaling (MDS) with the RAPFISH application and Participatory Prospective Analysis (PPA). The analysis reveals a sustainability score of 49.67, indicating poor sustainability performance. Furthermore, this research indicates that sustainability can be enhanced by taking into account factors beyond the economic aspect. One way to achieve this is by utilizing resources that are already available within these communities but have not yet been utilized. This research emphasizes the significance of local knowledge and the necessity to mitigate ecosystem damage. It adds to existing knowledge by demonstrating that utilizing local wisdom is crucial to achieving sustainability. The study highlights the importance of local knowledge as a valuable resource for conserving fisheries. To achieve sustainability, it is crucial to empower local wisdom and strengthen customary rules.